Decision making influences movement variability and performance of elite female football players in a ball resistance task - Tuyà Viñas, S.; Fernández-Valdés Villa, B.; Pérez-Chirinos Buxadé, C.; González, J.; Moras Feliu, G. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Nowadays, constraints are included in resistance training in order to develop strength within the context of sport and to maximise its effectiveness [1]. Considering that perceptual-cognitive abilities play a fundamental role in sport as they are directly related to individual and team success [2], decision making could be introduced in resistance training as a constraint to promote the development of the athletes abilities in a holistic way. Therefore, the aim of this study was to investigate the effects of the attacker and defender decision making on movement variability and performance during an elastic resisted forward-backward movement with ball in elite female football players.